Strategic analysis of the challenges facing the elements of the modern technical environment Kurdistan Region case study - Amanj younis Othman (QALAAI ZANIST JOURNAL, 2019)
This study examined the strategic analysis of the challenges facing the elements of the modern technical environment in the Kurdistan region, and aimed to try to identify the most important variables of the external environment and the internal environment of the auditing profession in light of modern technology in order to diagnose and analyze the challenges facing it to the development of the profession in Kurdistan. Using the deductive and inductive approach, I have reached a number of results and recommendations, the most important of which is the link between the strategic development of the profession and the exploitation of economic opportunities that are indirectly affected by it, such as the high rate of economic growth and the speed of technical development in light of Ed knowledge and increase the structure of local and foreign investments and increase the average per capita income. The profession needs to realize the most influential opportunities within it within the mission environment, which is represented by customers, suppliers, competitors, and seeking to exploit them when building its strategy. The profession’s awareness of the quality of information necessary for the growth and development process in light of the elements of the modern technical environment, which are reflected in the form of new services practiced by auditors, and the preparation, qualification and professional development commensurate with those required services